RP-HPLC Analysis of Temozolomide in Pharmaceutical Dosage Forms - Lakshmana Rao, A.; Taraka Ramesh, G.; Rao, J.V.L.N.S. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive and precise high performance liquid chromatographic method has been developed for the estimation of temozolomide in pharmaceutical dosage forms. In thismethod RP-C18 column (250 mm × 4.6 mm I.D., 5 μm particle size) with mobile phase consisting of acetate buffer and methanol in the ratio of 75:25 v/v in isocratic mode was used. The detection wavelength is 254 nm and the flow rate is 1 mL/min. In the range of 50-300 μg/mL, the linearity of temozolomide shows a correlation coefficient of 0.9998. The percentage recovery ranges from 98.99-102.02 %. The proposed method was validated by determining sensitivity, accuracy, precision and linearity. The proposed method is simple, fast, accurate, precise and reproducible hence can be applied for routine quality control analysis of temozolomide in pharmaceutical formulations.